An approach towards the synthesis of codinaeopsin derivatives as uniques tryptophan-polyketide anti-malarial compounds / Ummu Umairah M Hatta - M Hatta, Ummu Umairah (2024)
In this study, codinaeopsin was chosen as our synthetic target compound due to its unique tryptophan-tetramic acid, pyrrolidinone structure. Codinaeopsin was isolated from biological source which is white yemeri trees and obtaining the continuous supply of codinaeopsin is problematic due to the scarcity of product origin. Over the decade, there is only one successful total synthesis of codinaeopsin was reported involving a lengthy step. Thus, a new synthetic route had been developed to overcome the problem. A series of successive functional group modifications was performed which began with esterification of L-tryptophan by using methanol and thionyl chloride (100%), followed by condensation of the methyl ester utilizing the methyl malonyl chloride to furnish an intermediate diester. This diester is then reacted with sodium methoxide to furnish β,βdiketo pyrrolidinone, a crucial diketo pyrrolidinone ring template via Dieckmann cyclization reaction. Lastly, the tetramic acid type compound is achieved by decarboxylation of the β,β-diketo pyrrolidinone employing acetonitrile. All compounds were synthesized in moderate to good yield in 4 steps with an overall yield of 34.05%. Nevertheless, different pyrrolidinone-type compounds from different hydrazine salts were synthesized via hydrazination and all the compounds were produced in low to good yields. In brief, this research was designed to provide intriguing new pathways to prepare tetramic acid carbon skeleton of codinaeopsin and minimize the cost and shorten the route for synthesizing tetramic acid.